2009
DOI: 10.1128/aac.00377-09
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Properties of Dihydrophthalazine Antifolates, a Novel Family of Antibacterial Drugs

Abstract: Racemic 2,4-diaminopyrimidine dihydrophthalazine derivatives BAL0030543, BAL0030544, and BAL0030545 exhibited low in vitro MICs toward small, selected panels of Enterococcus faecalis, Enterococcus faecium, Streptococcus pneumoniae, Moraxella catarrhalis, and Mycobacterium avium, though the compounds were less active against Haemophilus influenzae. The constellation of dihydrofolate reductases (DHFRs) present in 20 enterococci and 40 staphylococci was analyzed and correlated with the antibacterial activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The impact of the F98Y mutation on (R)-RAB1 is consistent with recent observations with related phthalazine-based DHFR inhibitors, such as BAL0030543 (Fig. 2B) (7,9). While the three-dimensional structures with the BAL compounds are not known, they may use a similar binding mode such that the phthalazine group follows the path of RAB1 form 1, while the pyrimidine moiety extending from the phthalazine would occupy the same position as RAB1 form 2.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The impact of the F98Y mutation on (R)-RAB1 is consistent with recent observations with related phthalazine-based DHFR inhibitors, such as BAL0030543 (Fig. 2B) (7,9). While the three-dimensional structures with the BAL compounds are not known, they may use a similar binding mode such that the phthalazine group follows the path of RAB1 form 1, while the pyrimidine moiety extending from the phthalazine would occupy the same position as RAB1 form 2.…”
Section: Discussionsupporting
confidence: 71%
“…Concomitant with the current work, the broad-spectrum activities of related RAB1-like molecules have been demonstrated by Basilea Pharmaceutica International AG. These studies also highlighted the difficulty in generating spontaneous resistant mu-tations of chromosomal DHFR to inhibitors in the dihydrophthalazine series (7,9).…”
mentioning
confidence: 99%
“…Additionally, an Leu24Ile mutation was detected in the chromosomal DHFR of a clone of S. epidermidis strain CN051 for which BAL0030543 had an MIC of 64 g/ml (Table 6). Isoleucyl, isoleucyl, and asparaginyl residues occur at positions 20, 24, and 46, respectively, in the plasmid-encoded [dfr(G)] DHFR isozyme S3 (35), which is not inhibited by the dihydrophthalazines (11).…”
Section: Resultsmentioning
confidence: 99%
“…These novel compounds inhibited not only wild-type and mutant chromosomally encoded DHFRs in S. aureus [dfr(B)] and S. epidermidis [dfr(C)] but also the plasmid-borne DHFR isozyme S1 encoded by dfr(A), which is highly resistant to trimethoprim. Unlike trimethoprim, the dihydrophthalazines were active against staphylococci harboring a chromosomal DHFR Phe98Tyr mutation (11). With their good oral bioavailabilities and favorable pharmacological/toxicological properties (20), dihydrophthalazine antifolates BAL0030543, BAL0030544, and BAL0030545 are potentially attractive therapies for multidrug-resistant staphylococoal infections, including those for which long-term (Ͼ2-week) therapy is warranted.…”
mentioning
confidence: 99%
“…Depending on the species, either the folP1 gene or the sulI genes encode the mycobacterial type 1 DHPS. Although most of the data on the interaction of trimethoprim and sulfonamides come from nonmycobacterial species, several studies demonstrated that trimethoprim and sulfonamides bind to and inhibit the DHFR and DHPS of NTM (7,17,25,38,65,67,72,116,272,326,352).…”
Section: Inhibition Of Nucleic Acid Synthesismentioning
confidence: 99%